Non-inflammatory cerebrospinal fluid delays the diagnosis and start of immunotherapy in anti-NMDAR encephalitis - Mariana Espinola-Nadurille; Paola Bautista-Gomez; Jose Flores; Veronica Rivas-Alonso; Rodrigo Perez-Esparza; Rodolfo Solís-Vivanco; Steven Vargas-Cañas (Arquivos de Neuro-Psiquiatria)
ABSTRACT Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is a form of autoimmune encephalopathy that presents with a wide variety of symptoms, including neuropsychiatric manifestations. The authors’ aim for this study was to analyze the results of paraclinical studies of patients with a diagnosis of anti-NMDAR encephalitis and the association between symptom onset and diagnosis, and start of immunotherapy. Retrospective data of 29 patients with anti-NMDAR encephalitis were gathered and analyzed. Abnormal EEG was found in 27 patients (93.1%), whereas MRI was abnormal in 19 patients (65.5%). In contrast, an inflammatory pattern on CSF analysis was found in only 13 patients (44.8%). The absence of pleocytosis or increased proteins in the CSF was associated with a longer time from symptom onset to diagnosis and treatment (p = 0.003). The authors conclude that noninflammatory CSF may delay the correct diagnosis and start of immunotherapy in anti-NMDAR encephalitis. In the presence of suggestive clinical features, extensive studies including EEG are recommended.